2006
DOI: 10.1097/01.mib.0000201098.26450.ae
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective survey of 452 patients with inflammatory bowel disease in Wuhan City, central China

Abstract: The prevalence of IBD has increased in Wuhan City, central China, but is not as high as in Western countries. The disease in Wuhan City has often been associated with young adult professional males with a high level of education. The clinical presentation of UC was often mild and had few extra intestinal manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
127
6
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(160 citation statements)
references
References 28 publications
(50 reference statements)
18
127
6
9
Order By: Relevance
“…(25) It is possible that these earlier reports extrapolated to paediatric patients the interpretations of other studies that had found a higher prevalence of UC among Asian adults. (15,26,27) However, the proportion of patients with CD and UC in our study (15:1) was much higher than that in the United Kingdom (2:1), indicating perhaps that paediatric patients with UC were under-represented in our study. (25) It is possible that some of our patients with UC were misdiagnosed and treated for infective diarrhoea, and thus…”
Section: Discussioncontrasting
confidence: 47%
“…(25) It is possible that these earlier reports extrapolated to paediatric patients the interpretations of other studies that had found a higher prevalence of UC among Asian adults. (15,26,27) However, the proportion of patients with CD and UC in our study (15:1) was much higher than that in the United Kingdom (2:1), indicating perhaps that paediatric patients with UC were under-represented in our study. (25) It is possible that some of our patients with UC were misdiagnosed and treated for infective diarrhoea, and thus…”
Section: Discussioncontrasting
confidence: 47%
“…The peak incidence of CD of both genders in our cohort was in the second and third decades of life, which is in accord with that in North American CD patients (23) . But, the feature of bimodal distribution of the age at presentation appeared in the previous western study by Farrokhyar et al was not observed in either sex in our cohort, which is in concordant to another previous Chinese study (12,16) CD has a predilection to affect young persons, which accounts the fact that the patients of our cohort had low prevalence of comorbidities. Apparently more male patients had a positive smoking history, that was in line with our general population and such gender-related differential rates of smoking might result in the male predominance of CD in our series.…”
Section: Discussionsupporting
confidence: 78%
“…Congruent with previous Asian studies, including data from China (14,16,24,46) , Japan (2,15,27,43) , Korea (42,44) , Singapore (21) , India (9) and Sri Lanka (35) , our observation have demonstrated a male predominance in CD, which is discordant with majority of the western studies. Such discrepancy may be sex-related differences in triggering or predisposing factors of CD between Asian and Western populations.…”
Section: Discussioncontrasting
confidence: 36%
“…In the literature, only 3% of UC patients required surgery, whereas 27% of CD patients underwent surgical procedures (p<0,001) (21). Both extraintestinal and local complications were more frequent in CD patients, whereas arthritis was the most common EIM in both diseases (23).…”
Section: Discussionmentioning
confidence: 99%